Research on the transverse flexural performance of T-PBL joints between corrugated steel webs and concrete slabs. (October 2022) - Changyu, Wang; Shiping, Yin; Boxue, Wang; Jianhua, Du; Xiaoping, Ren; Xiaoliang, Zhang
Abstract: To study the transverse flexural performance of the T-PBL joint between a corrugated steel web and a concrete slab, taking the diameter of the perforated rebar, the type of perforated bars, the strength of the concrete and the type of connector as the research parameters, four groups of 10 1:1 full-scale model specimens of the joint between the corrugated steel web and concrete slab were tested. The experimental results show that the failure of the joint of the corrugated steel web and concrete slab specimens under the action of the transverse bending moment mainly occurs on the tensile side, which is mainly manifested as a concrete tension crack on the tensile side. The transverse flexural capacity of the T-PBL joint can be improved by increasing the diameter of the perforated rebar and the strength of the concrete. The failure mode of the specimens with ordinary perforated rebar is ductile failure, while the specimens with FRP perforated bars exhibit brittle failure, and the transverse flexural capacity and ductility of FRP bars are relatively low. The transverse flexural performance of the T-PBL joint is better than that of the stud connector joint and embedded connector joint. At present, the factors and calculation methods considered in the existing calculation formulas are different. Based on the test results in this paper, the existing theoretical calculation formulas for the T-PBL joint of corrugated steel webs and concrete slabs are compared and analyzed. It can be seen that the calculated value of the formula combining the formula proposed in the Chinese standard and the Medberry formula has the best agreement with the test value.